1999
DOI: 10.1002/hep.510290627
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Thrombopoietin Mrna Levels in Acute and Chronic Liver Failure of Childhood

Abstract: The liver is the main production site of the hormone thrombopoietin (TPO), the major regulator of megakaryopoiesis. To investigate the role of an impaired TPO gene expression in the pathogenesis of thrombocytopenia in pediatric patients suffering from liver failure, we measured hepatic TPO mRNA in children with acute or chronic end-stage liver disease undergoing orthotopic liver transplantation. Tissue samples for RNA extraction were obtained from 12 children with compensated cirrhosis (CC), 22 children with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
3
46
0
Order By: Relevance
“…In cirrhosis, there is a decrease in functional hepatocytes. A correlation between decreases in serum levels of TPO with platelet counts has been found by Wolber et al [16] during transition from compensated to decompensated cirrhosis.…”
Section: Hepatic Dysfunctionsupporting
confidence: 52%
“…In cirrhosis, there is a decrease in functional hepatocytes. A correlation between decreases in serum levels of TPO with platelet counts has been found by Wolber et al [16] during transition from compensated to decompensated cirrhosis.…”
Section: Hepatic Dysfunctionsupporting
confidence: 52%
“…Extrahepatic TPO production is thought to be limited 3 but has not been studied in ALF; a clinical study found decreased hepatic TPO messenger RNA levels in children with ALF compared with cirrhosis. 13 We suggest that studying hepatic versus extrahepatic TPO production in animal models of ALF might clarify this issue.…”
Section: Discussionmentioning
confidence: 98%
“…43 Further, a number of inflammatory states (eg, ulcerative colitis, rheumatoid arthritis, and ovarian cancer) are associated with increased blood TPO levels and thrombocytosis. 1,38,[44][45][46][47][48][49][50][51] This inflammation-induced increase in TPO expression is mediated by IL-6, which stimulates hepatic TPO messenger RNA (mRNA) expression and production both in hepatocytes in vivo and in hepatoma HepG2 and Hep3B cells in vitro. 49,50,52,53 If hepatic TPO regulation by IL-6 is now well characterized, the ligand-receptor pair regulating hepatic TPO production at steady state has remained elusive.…”
Section: Fl/flmentioning
confidence: 99%